The Pioneering Formulation of the Concepts of Secularity and Secularism in the Arab-Islamicate World(s): Butrus al-Bustani's The Clarion of Syria - Darwish, Housamedden (Religions, 2023)
This paper critically discusses the pioneering formulation of secularity and secularism in the Arab-Islamicate world(s) found in Butrus al-Bustani’s The Clarion of Syria (1860–1861). This discussion is conceptually based on the distinction between ‘secularity’ as an analytical concept, and ‘secularism’ as a normative and ideological concept. Here, secularity is understood to refer to (structural) distinctions, whether practical or theoretical or cognitive, between the religious and the non-religious. Secularism refers to the ideological promotion of such a differentiation and distinction between religion and, in particular, politics or the state. This paper provides a conceptual analysis of secularity, secularism, and secularization, highlighting the differences between them, as well as the epistemological and methodological requirements for drawing a distinction between them in modern and contemporary Arab thought. It also reflects on the linguistic and historical context, looking at the concepts of secularity and secularism in Arab thought prior to al-Bustani’s The Clarion of Syria.